Characteristics of information manager / Siti Khadijah Mazlan and Muhammad Hisyamuddin Mohammed Noor - Mazlan, Siti Khadijah; Mohammed Noor, Muhammad Hisyamuddin (Faculty of Information Management, 2014)
According to Charles Handy (1992) manager is "A manger shapes and shares a vision which gives point to the work of others" "Besides that manager also known as an individual influences a group of individuals to achieve a common goal. 'An individual in this context is referring to the leader for community college lecturers, 'the group of individuals'. It would he the community college students and 'the common goal here is the process to educate, bringing the students to a higher level of their life, to equip them with the necessary knowledge they would need in their later career life.